The Incidence Of Hepatitis B Surface Antigen Positive Pregnant Women Admitted and Delivered at Camiguin General Hospital, Mambajao, Camiguin - Bandiola, Expeditha I.; Ambal, Charlotte C. (JPAIR Multidisciplinary Research, 2008)
This study sought to investigate the incidence of mothers who are Hepatitis B surface antigen positive at Camiguin General Hospital for the month of December 2005 and January 2006. This study sought to find out cases of pregnant women with positive hepatitis B surface antigen who delivered at Camiguin General Hospita, number of babies born from mothers who are positive of hepatitis B surface antigen, and were given immunoprophylaxis 12 hours after delivery, and the profile of the mothers who had hepatitis B surface antigen positive as to age, educational status, economic status and awareness of the result of hepatitis B surface antigen. Pregnant women admitted were checked up if they are positive of Hepatitis B surface antigen and the study reveals that out of seventy (70) pregnant mothers admitted and delivered, fifty-eight (58) were examined for Hepatitis B surface antigen and twelve (12) were not examined. Three (3) of the mothers were found positive of Hepatitis B surface antigen with three (3) babies born from mothers who are positive for Hepatitis B surface antigen and were given Hepatitis B vaccine with a dose of 0.5 ml and Hepatitis B immunoglobulin with a dose of 0.5 ml at birth. The three mothers are in their early twenties, single, first time mothers, undergraduates and jobless and knew the result of the Hepatitis B surface antigen prior to delivery.